Effect of Cryogenic Freezing on Food: a Review - S, Kumar (Journal of Postharvest Technology, 2024)
Food materials are perishable by nature. They require processing  or preservation techniques to enhance the storage life. Cryogenics  is a branch of engineering wherein production of cryogen and the  maintenance of low temperature technologies are studied. Such  cryogens have a tremendous potential to be used as a total loss  refrigerant. Implementing cryogenic solutions in the field of high volume/high-quality food processing is important for a number of  reasons. Maintaining proper food temperatures throughout the  plant is essential for food preservation and food safety. These are  fundamental elements for consistent food quality and the  hallmark of top quality. At the same time, high-efficiency  cryogenic processes using either carbon dioxide (CO2) or liquid  nitrogen (N2) can boost productivity and streamline operations.
Keywords: Cryogen,; Liquid nitrogen; Food freezing,; Food quality